2015 33rd IEEE International Conference on Computer Design (ICCD) 2015
DOI: 10.1109/iccd.2015.7357117
|View full text |Cite
|
Sign up to set email alerts
|

From theory to practice of private circuit: A cautionary note

Abstract: Private circuits, from their publication, have been really popular among the researchers. They also form the basis for provable masking schemes. There are several works which try to improve the results of bit-level private circuits based on 2-input gates for the combinational logic. However, strangely, no practical side-channel analysis of private circuits has been presented so far, which is the focus of the present paper. In this paper, we have tried to identify the 'ambush' or hidden dangers in the implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Previous work has shown that applying PC-I or PC-II is not trivial and prone to many subtle mistakes that can lead to insecure designs. As the traps and pitfalls of PC-I were covered in the work of Roy et al [29], we direct our focus on PC-II.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work has shown that applying PC-I or PC-II is not trivial and prone to many subtle mistakes that can lead to insecure designs. As the traps and pitfalls of PC-I were covered in the work of Roy et al [29], we direct our focus on PC-II.…”
Section: Discussionmentioning
confidence: 99%
“…the operation order by inserting registers. In [29], a secure AND gadget was proposed by inserting registers behind every gate of a manually encoded PC-I AND. The resulting impact on the area and performance is significant.…”
Section: B Masking With Private Circuitsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 3, we do this first for various masked S-box implementations. The results from other works are obtained by synthesis, translate and map using Xilinx default settings apart from the KEEP HIERARCHY constraint which is turned on to prohibit optimization across shares [50], as is common practice with masked implementations [22, §2.4.1]. We stress that no optimization for FPGA has been done for these designs.…”
Section: Methodsmentioning
confidence: 99%